2020
DOI: 10.22219/kinetik.v5i4.1120
|View full text |Cite
|
Sign up to set email alerts
|

Mental Disorder Detection via Social Media Mining using Deep Learning

Abstract: Mental disorders are a disease that cannot be physically seen, so diagnosing someone with a mental disorder is not easy. Due to the imperceptible nature of mental disorders, diagnosing a patient with a mental disorder is a challenging task. Therefore, detection in people with mental disorders can be done by looking at the symptoms they experience. One symptom in patients with mental disorders is solitude. Patients with mental disorders feel indifferent to their environment and focus on what is happening to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Figure 1 showing the study stage from the data crawling phase to the evaluation phase. The system consists of four main parts covering the processes of data collection, feature extraction, data labeling, and data classification using deep learning [19]. This study used three datasets, namely the Anies Baswedan, Ganjar Pranowo, and Prabowo Subianto datasets.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 showing the study stage from the data crawling phase to the evaluation phase. The system consists of four main parts covering the processes of data collection, feature extraction, data labeling, and data classification using deep learning [19]. This study used three datasets, namely the Anies Baswedan, Ganjar Pranowo, and Prabowo Subianto datasets.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, authors demonstrated that the use of sentiments, emotions, and negative words in users everyday posts is prominent in determining the level of depression. The classification model was constructed using long short-term memory, a deep learning algorithm which generated an accuracy of 70.89%, precision of 50.24%, and recall 70.89% (Kholifah et al, 2020). In another recent investigation of dataset retrieved from Twitter highlighted posts related to mental risk and by applying multiple instance learning with anaphoric resolution encoder researchers achieved 92% accuracy (Wongkoblap et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%